Play Me Something Quick and Devilish : Old-Time Fiddlers in Missouri - Marshall, Howard W. (Book collections on Project MUSE., 2012)
Beginning with the French villages on the Mississippi River, the author explores the heritage of traditional fiddle music in Missouri. Leading us chronologically through the settlement of the state, Marshall considers the place of homemade music in people's lives across social and ethnic communities from the late 1700s to the World War I years and into the early 1920s. Through the settlement of the state of Missouri, Marshall investigates how these communities established our cultural heritage, the "Old Stock Americans," (primarily Scotch-Irish from Kentucky, Tennessee, North Carolina, and Virginia) ; African Americans, German-speaking immigrants, people with American Indian ancestry (focusing on Cherokee families dating from the Trail of Tears in the 1830s), and Irish railroad workers in the post-Civil War period. These are the primary communities whose fiddle and dance traditions came together on the Missouri frontier to cultivate the bounty of old-time fiddling enjoyed today.